THE EFFECT OF THE EXISTENCE OF WOMEN BOARD OF DIRECTORS IN THE BOARD OF DIRECTORS ON ACCURAL EARNINGS MANAGEMENT - Jessica Jusup; Elfina Astrella Sambuaga (Jurnal Akuntansi, 2022)
The purpose of this study was to examine whether there is an effect on the presence of women on the board of directors and the percentage of women directors on accrual earnings management behavior. This research begins with the assumption that the presence of women on the board of directors and the percentage of women board of directors can reduce the occurrence of earnings management practices, by taking samples using companies that are included in LQ 45 during 2016-2020, so the number of observations is 115, and using purposive sampling as a data collection technique. Based on the two proposed hypotheses, the existence of female directors has a negative effect on accrual earnings management behavior and the percentage of female directors has a negative effect on earnings management behavior. Therefore, the results of the study show that the presence of women on the board of directors has a negative effect on earnings management, while the percentage of female directors has a positive effect on earnings management.